Urban regeneration in Castelo Branco’s civic centre, a challenge to the city’s transformation - Belo, Alexandra Paisana (2019)
Castelo Branco was the target of a POLIS operation, concerning its centre’s requalification. After its conclusion, the City Hall continued to engage in urban revitalization, intending to improve competitiveness. The latest instruments face urban regeneration as a whole, identifying and connecting new centralities. Besides, the requalified equipments and public spaces need to be well used. Its programming presents itself a strategy challenge. The latest cultural and heritage investments aim to enhance the city’s touristic potential, creating a brand image and alternatively stimulating the economy. This paper will analyse the impact of urban regeneration in Castelo Branco’s public space, comparing it to its previous context and pointing out trends. To that end, different theories, planning instruments and programs related to this theme will be studied. Considering a critical approach, the advantages and disadvantages of the urban strategy that was led and still is in process, will also be taken into consideration.